The Watershed of Bais City - Cadeliña, Angelita M. (Silliman Journal, 2023)
One of the two most highly biodiversified ecosystems of the earth is the tropical moist forest. The forest as an ecosystem supports millions of species (IUCN 1990). Its severe alteration by man brings about the most disastrous effects to the entire earth’s ecosystem, including the marine ecosystem. The loss of species diversity due to habitat disappearance on account of anthropogenic activities is tremendous, not counting the effects on climate, shelter, water and food supply.